Development of an online catalog of the Diliman Interactive Learning Center's collection based on learning object metadata - Surmieda, Janny S.; Angeles, Chito N. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2008)
The main goal of the study was to create an online catalog for the collection for Diliman Interactive Learning Center (DILC) using Learning Object Metadata (LOM). Among its objectives were to enumerate the fields of LOM that would be able to describe the collection of DILC and to enumerate the functionality and features needed in the online catalog.
The researcher used questionnaires in gathering information from the respondents. The study had two main groups of respondents, the DILC staff and the student users of the Learning Materials. Rapid Application Development was used in the development of the system.
The data gathered from the survey revealed that all the fields in the general category, life cycle category, meta-metadata category, technical category, educational category, rights category, relation category, annotation category and classification category were needed in describing the Learning Materials. The survey also revealed that combined searching and Boolean searching were the functions needed by both the DILC staff and student respondents. Further functions such as different username and password for each DILC staff were needed.
Recommendation included were to further broaden the respondents of the survey and to include those who were not from UP who use the Learning Materials. Another is the writing of a user's manual for the online collection catalog. The researcher also recommends that other studies be done using other metadata element set.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: UP Diliman Interactive Learning Center; Metadata -- Philippines -- Quezon City; Online library catalogs -- Subject access -- Philippines -- Quezon City